Bahasa Slang di Angkringan Kabupaten Ponorogo - Heru Setiawan (Madah: Jurnal Bahasa dan Sastra, 2019)
This research examines and discovers the variation and formation of slang in the street food court (angkringan) of the Perpek community, Ponorogo Regency, which is indicated by a variant of the slang language. This research uses a qualitative descriptive method. The research data is in the form of words from languages that contain slang forms and are spoken by sellers and buyers. Data collection uses observation techniques supported by note-taking techniques. The data analysis technique used is the equivalent method and the method of religion. The findings of this research are four processes of the formation of slang language in terms of the formation of phonological structures, namely: (1) reversing the overall arrangement of letters, for example "mahal" to "laham", (2) giving an insert at the beginning and at the end both vowels and consonants, for example "kopi" becomes "ngikop", (3) exchanges consonants and replaces one or two letters, for example "sedikit" becomes "sikit", and (4) words are shortened or cut without changing their meanings, for example "mama cantik" to be "macan". The results of the research findings indicate the formation of new slang languages that are different from the original languages, both from Indonesian and regional languages (Javanese).